A Review of Solar PV-Grid Parity in Akure, South-West Nigeria - Adegoke Oladipo Melodi; Sola Richard Famakin (Institute of Advanced Engineering and Science, 2015)
The abundance of solar energy in Akure, South-West Nigeria and its feasibility as an alternative energy source has been proven. However, cheap, Government subsidized but unreliable grid electricity and high cost of solar equipment are considered the major hindrances to deployment of solar energy for improved power supply and environmental sustainability. An earlier work pointed out realistic pricing of electricity, reduced cost of solar equipment and reduction in solar cell degradation factor as major factors capable of speeding up parity hence, motivating solar energy consumption. It showed that parity is attainable within 14 years. Documented significant improvements in these factors in recent times are the motivations for this review. This review cost-comparatively re-assesses both sources of energy under the prevailing National electricity policy and market realities using simple mathematical and graphical modeling techniques. This is with a view to determining a new timing for parity of solar energy with grid supply. Results showed that solar PV-grid energy cost parity is now attainable within 6 years in the study region. It was also observed that sustained improvement in grid energy unit cost and reduction in cost of solar equipment and accessories may accelerate solar-grid energy parity to less than three years.